1994
DOI: 10.1007/bf00040331
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the bamboo Chusquea culeou (Poaceae: Bambusoideae) in southern Argentina

Abstract: Over a period of 7 years the biology and phenotypic variability of Chusquea culeou were studied at 5 locations in cool temperate forests of southern Argentina. Excavated rhizomes had an average of 1.1 successful rhizome buds, and an average of 2.1 years elapsed between successive generations of rhizomes. Rhizome buds usually develop within the first four years after a rhizome forms. Height, volume and weight of a culm can be calculated from its diameter 1 m above the ground. Culm size, length of foliage leaf b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 14 publications
3
68
0
7
Order By: Relevance
“…Consistent differences in leaf morphology and anatomy were observed between sun and shade plants or leaves in Y. niitakayamensis, C. culeou and P. aurea. The smaller leaf size, thicker leaf blades and closer vein spacing found in sun leaves are consistent with findings in other taxa exhibiting sun-shade variation, including the strong negative correlation between mean leaf length and light intensity index observed by Pearson et al (1994) in C. culeou.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent differences in leaf morphology and anatomy were observed between sun and shade plants or leaves in Y. niitakayamensis, C. culeou and P. aurea. The smaller leaf size, thicker leaf blades and closer vein spacing found in sun leaves are consistent with findings in other taxa exhibiting sun-shade variation, including the strong negative correlation between mean leaf length and light intensity index observed by Pearson et al (1994) in C. culeou.…”
Section: Discussionsupporting
confidence: 89%
“…Preliminary observations of two species of woody bamboos, Yushania niitakayamensis and Chusquea culeou, which occur in both shaded forest understoreys and adjacent clearings and grasslands (Lin 1978, Chen 1989, Pearson et al 1994, revealed morphological and anatomical variation between sun and shade leaves, especially with respect to the presence or absence of fusoid cells. In our studies, we also included Phyllostachys aurea (an Asian bamboo now widely cultivated) because of its putative lack of fusoid cells, and Bambusa longispiculata (another Asian bamboo often found in cultivation) because of its relatively large fusoid cells.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of the synchronized flowering and fruiting are intensely debated in the literature, and the probable evolutionary explanations for the phenomenon include predator satiation (Janzen 1976), escape from parasites (Pearson et al 1994) and the fire cycle hypothesis (Keeley & Bond 1999). Moreover, synchronized flowering has been referenced as an advantage assuring the efficiency of wind pollination (Waller 1993, Kelly et al 2001, Koenig & Ashley 2003 as seems to be the case in A. aristulata.…”
Section: Discussionmentioning
confidence: 99%
“…At mean while, multiple ecologic functions had been provided by bamboo forests in cultivation arers (Kleinhenz and Midmore 2001). Due to its great potential for rapid biomass production (Pearson et al 1994;Scurlock et al 2000), bamboo is a vital net carbon sink under global climate change (Isagi et al 1997;Chen et al 2009;Zhuang et al 2011). Some researchers reported that bamboo forests, such as mao bamboo forest, have more efficient carbon sequestration than typical temperate forests, like Chinese fire and mason pine, in southern China (Zhou and Jiang 2004).…”
Section: Introductionmentioning
confidence: 99%